Aortic Geometric Alteration Associated With Acute Type B Aortic Dissection: Angulation, Tortuosity, and Arch Type - Sun, Likun; Li, Jiehua; Wang, Lunchang; Li, Quanming; He, Hao; Li, Xin; Li, Ming; Wang, Tun; Zhao, Chenglei; Zhang, Xiaolong; Shu, Chang (Frontiers in Physiology, 2021)
Background: Acute type B aortic dissection (aTBAD) is a highly serious aortic pathology. Aortic geometric parameters may be useful variables related to occurrence of aTBAD. The aim of the study is to delineate the alteration in aortic geometric parameters and analyze the specific geometric factors associated with aTBAD. Methods: The propensity score matching (PSM) method was applied to control confounding factors. The aortic diameter, length, angulation, tortuosity and type of aortic arch of the aTBAD and control group was retrospectively analyzed via three-dimensional computed tomography imaging created by 3mensio software. The geometric variables of true lumen and false lumen in the descending aorta were measured to estimate the severity of aortic dissection. Multivariable logistic regression models were conducted to investigate the significant and specific factors associated with aTBAD occurrence. The area under the receiver operating characteristic curve (AUC) was used to estimate the model performance. Results: After PSM, 168 matched pairs of patients were selected. The ascending aorta and aortic arch diameters were dilated and the ascending aorta and total aorta lengths were elongated in aTBAD group significantly (P < 0.001). The ascending aorta and aortic arch angulations in aTBAD group were sharper versus controls (P = 0.01, P < 0.001, respectively). The aortic arch and total aorta tortuosities were significantly higher in aTBAD group. There were more type Ⅲ arch patients in aTBAD group than controls. The true lumen angulation was sharper than that in the false lumen (P < 0.01). The true lumen tortuosity was significantly lower than that in the false lumen (P < 0.001). Multivariable models identified that aortic arch angulation, tortuosity and type Ⅲ arch were independent and specific geometric factors associated with aTBAD occurrence. AUC of the multivariable model 1, 2, 3 were 0.945, 0.953 and 0.960, respectively. Conclusions: The sharper angulation and higher tortuosity of aortic arch and type Ⅲ arch were the geometric factors associated with aTBAD in addition to the ascending aorta elongation and aortic arch dilation. The angulation and tortuosity of the true and false lumen may carry significant clinical implications for the treatment and prognosis of aTBAD.